Security concerns and trust in the adoption of m-commerce - Alexios Vasileiadis (Social Technologies, 2014)
Purpose – to deeply examine customers’ perception in terms of how the determinants of trust and perceived risk affect their intention to adopt mobile commerce. Design/methodology/approach – literature review, conceptual framework, modelling method, quantitative survey methodology (questionnaire instrument). Findings – the perception of risk in terms of privacy, m-payments, m-commerce legislation and quality of delivered products has negative effect in the intention to adopt mobile commerce, while the good online vendors’ reputation, enticing promises, good encryption security and transparency, reduce the effect of risk and increase the intention to use m-commerce. The availability of easy to understand and find policies have positive effect in the intention to use m-commerce. When customers feel free of risks and have high level of trust in the intention to use mobile commerce they actually adopt it. Research limitation/implications –this empirical research contributed to the theory by exploring which factors influence or deter the m-commerce adoption. However, the UTAUT model, simple random sampling method and case studies on how the online vendors perform towards this topic are worth-exploring by future researchers. Practical implications – the research results show that mobile technology manufacturers and developers should improve both software and wireless network security, online vendors should improve their online reputation, transparency, and mobile website navigation. Lawmakers should improve m-commerce legislation to better protect customers in case of dispute with online vendors. Originality/value – previous researchers have never focused solely and in-depth on the determinants of perceived risk and trust. Moreover, this object had never been examined in the Greek Population. Keywords: mobile commerce adoption, security concerns, trust, perceived risks Research type: literature review, Conceptual paper, Research paper